Advances in CoP electrocatalysts for water splitting. (June 2021) - Li, Z.; Feng, H.; Song, M.; He, C.; Zhuang, W.; Tian, L.
Abstract: With increase in research on electrocatalytic water splitting, exploiting cost-effective, highly active, and stable electrocatalysts for oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) becomes a popular topic in addition to main catalyst research. Transition metal phosphides, particularly for cobalt phosphide nanocatalysts, are attracting intense interest owing to their abundance in the earth's crust and comparable catalytic properties with those of noble metals. In this review, the fundamentals of overall water splitting, including the reaction mechanisms and evaluating parameters of OER and HER, are systematically discussed. In addition, an overview of the synthesis approaches is also provided to afford guidance for future fabrication of high-performance cobalt phosphide nanocatalysts. Next, some mechanistic studies of the catalytic active sites of cobalt phosphide nanocatalysts are also discussed to give insight into the nature of active catalytic centers, and some advanced strategies with regard to further improving the electrocatalytic properties have also been summarized in detail. Finally, a summary of the challenges and future directions of cobalt phosphide nanocatalysts for practical applications are also summarized. It is expected to afford guidance for further improvement of electrocatalytic properties of cobalt phosphide electrocatalysts and use in practical applications. Graphical abstract: Image 1 Highlights: Recent progress of advanced CoP catalysts for water splitting is briefly reviewed. The advantages of CoP toward water splitting are highlighted. Mechanisms of overall water splitting are systematically illustrated. Suggestions for future research that might help to further develop water-splitting electrocatalysts are discussed.